The Effect of Temperature on the Physiological Condition and Immune-Capacity of European Lobsters (Homarus gammarus) During Long-Term Starvation - Albalat, Amaya; Johnson, Laura; Coates, Christopher J.; Dykes, Gregory C.; Hitte, Fiona; Morro, Bernat; Dick, James; Todd, Keith; Neil, Douglas M. (Frontiers in Marine Science, 2019)
Decapod crustaceans, such as those from the Homarus genus, are key benthic representatives supporting very valuable fishing and aquaculture industries. Those commercially caught, such as the European lobster (H. gammarus) can be stored in live facilities for short (few days) to long periods (up to 6 months) before being traded. Conditions in captivity are not standardized, including holding temperatures or feeding regimes. Herein, the physiological condition during long-term starvation (24 weeks) in H. gammarus was assessed at three temperatures (4, 8 and 12°C). Our results indicate that, H. gammarus have the capacity to endure long-term starvation. Principal component analysis (PCA) of measured parameters showed two main components (Eigen value>1). Fasted animals kept at 12°C separated from all others experimental groups due to higher total phenoloxidase (PO) activity in the hemolymph and water content in the muscle, suggesting that keeping H. gammarus un-fed at this higher temperature is physiologically more demanding and detrimental. This was later confirmed by significant changes particularly in this group in histology and lipid class composition of the hepatopancreas. These data call into question the suitability of current accepted in-vivo condition markers (e.g. hemolymph protein concentration) for determining the physiological condition and welfare of decapods such as H. gammarus.